A practical ortho-acylation of aryl iodides enabled by moisture-insensitive activated esters via palladium/norbornene catalysis. Issue 21 (29th September 2020) - Feng, Yunxia; Wang, Yangyang; Zhao, Shen; Zhang, Dao-Peng; Li, Xinjin; Liu, Hui; Dong, Yunhui; Sun, Feng-Gang
Abstract : Herein reported is a practical Catellani-type ortho -acylation of aryl iodides enabled by employing moisture-insensitive esters as the electrophile via C(O)–O bond cleavage. Abstract : A novel ortho -arene C–H acylation of aryl iodides catalyzed by the palladium/norbornene cooperative system by employing triazine esters has been developed, leading to the synthesis of polysubstituted aryl ketones. This ortho -acylation even proceeds smoothly in water. Preliminary mechanistic experiments indicate that the strong electron-withdrawing ability and coordination chemistry of triazine play crucial roles in this transformation.